Local tendon transfer for knee extensor mechanism reconstruction after soft tissue sarcoma resection - Fischer, Sebastian; Seitz, Christoph (Journal of plastic, reconstructive & aesthetic surgery, 2015)
Aim of this study was to measure the outcome of hamstring transfer for quadriceps reconstruction after soft tissue sarcoma resection and to identify risk factors influencing postoperative results. 43 patients underwent hamstring transfer after sarcoma resection. Medical records were reviewed for surgical technique and complications. Physical examination included assessment of range of motion and muscle strength as well as plantar pressure distribution by computerized dynamometer and podometry, respectively. Additionally, patients' satisfaction, quality of life and karnofsky index were assessed. Sole biceps transfer was performed in 31 (74%) and combined biceps/semitendinosus or gracilis transfer in 12 patients (26%). In 91%of cases 3/4 or more of the quadriceps muscle had to be removed. Postoperative complications occurred in 16 patients (37%). 17 patients (40%) were available for physical examination. Mean follow-up was 61 months (22-107). Average knee flexion was 74° (35-110°). All patients had full knee extension. Average extension force was 44% (19-79%) and flexion-force 74% (55-100%) of the unaffected leg. Mean plantar pressure distribution was 119% (44-200%) on the forefoot and 107% (60-169%) on the heel. Average patient satisfaction score was 16 (9-25), quality of life assessment was 78 (54-92) and Karnofsky Index was 82% (70-90%). Besides patient's age and the extent of resection, the surgical technique had statistically significant influence on functional outcome and postoperative complications (p < 0.05). Hamstring transfer is feasible for quadriceps reconstruction after massive tumor resection from the thigh. In contrast to biceps alone, combined semitendinosus or gracilis transfer revealed comparable outcome but higher complication rates.